Βιβλιοκρισία:F. LAURITZEN, The Depiction of Character in the Chronographia of Michael Psellos [ΒΥΖΑΝΤΙΟS. Studies in Byzantine History and Civilization 7], Turnhout 2013, σελ. Χ+260. ΙSBN 978-2-503-54841-8 - ΚΙΑΠΙΔΟΥ, Ειρήνη-Σοφία (Byzantina Symmeikta, 2016)
Βιβλιοκρισία:F. Lauritzen, The Depiction of Character in the Chronographia of Michael Psellos [ΒΥΖΑΝΤΙΟS. Studies in Byzantine History and Civilization 7], Turnhout 2013, σελ. Χ+260. ΙSBN 978-2-503-54841-8